The mitochondrial genome of Culter oxycephaloides (Cypriniformes, Cyprinidae) - Chen, Huijuan (Mitochondrial DNA B Resour, 2019)
In the present study, the complete mitogenome sequence of Culter oxycephaloides was determined using PCR amplification and DNA sequencing, which contains 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a non-coding control region with the total length of 16,619 bp. Except for eight tRNA and ND6 genes, all other mitochondrial genes are encoded on the heavy strand. The codon usage followed the typical vertebrate mitochondrial pattern (ATG or GTG for start codon and TAA or TAG for stop codon). There are 12 regions of gene share totalling 55 bp and 11 intergenic spacer regions totalling 84 bp. The complete mitochondrial genome sequence is useful for phylogenetic analysis and studies of population genetics of C. oxycephaloides.